Pendidikan Berbasis Kasih Sayang (Rahmatan Lil ‘Alamin) dalam Mengikis Mata Rantai Bullying di Institusi Pendidikan Islam - Jumi Romelah; Haekal Amirul Akbar; Hijriana Rahmah Amelia; Syamsul Arifin (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the concept of compassion-based education (rahmatan lil ‘alamin) from the perspective of Islamic educational philosophy and its relevance to bullying prevention in Islamic educational institutions. The study is motivated by the tendency of modern education to emphasize cognitive achievement while giving less attention to moral and affective development, resulting in the persistence of bullying behavior in educational settings. This study employs a qualitative approach using library research. Data were collected from the works of Muslim scholars, scientific journals, and relevant literature on Islamic education and analyzed through content analysis. The findings reveal that compassion-based education is built upon the integration of moral development, purification of the heart, and the cultivation of adab (proper conduct). These elements contribute to the development of empathy, social concern, and moral awareness among students. Therefore, compassion-based education (rahmatan lil ‘alamin) has strong relevance as a preventive approach to reducing bullying behavior and fostering a more humane and supportive educational environment in Islamic educational institutions.